An MCDA approach for identifying gaps and perspectives on the asthma treatment in Brazil - Silva Valentim Sallum, Frederico; Aparecido Oliveira, Wender; Ferreira Penha, Márcio; Gatti de Menezes, Fabiana (JORNAL DE ASSISTÊNCIA FARMACÊUTICA E FARMACOECONOMIA, 2025)
Introduction: Asthma is a chronic respiratory disease that has drawn attention due to the number of cases in Brazil and worldwide. Different treatments for asthma have been submitted to the Brazilian National Committee Health Technologies Incorporation (Coni-tec) from the Brazilian public healthcare system perspective. Objective: This paper aims to analyze the asthma appraisal reports in the Conitec database from February 2012 to May 2021 for classifying the main analysis criteria as strong or weak point for each technology. Methods: A search on the Conitec database for appraisal reports of asthma treatments has been undertaken. Then, a multi-criteria decision analysis (MCDA) fra-mework has been established for classifying each criterion as strong or weak point for each technology. Results: Nine asthma appraisal reports have been found on Conitec database for the submission of ten technologies forming a set of alternatives: three oma-lizumab submissions (2013; 2016; 2019), two fluticasone submissions (2013; 2015), two budesonide formoterol submissions (2015; 2021), tiotropium, benralizumab, me-polizumab (2021). Besides, the following set of criteria has been established: efficacy, safety, economic evaluation, budget impact. All criteria have been classified as strong point for tiotropium and benralizumab and classified as weak point for first fluticasone submission. Conclusion: It was possible to classify each criterion as strong or weak point for each technology submitted to Conitec. The proposal analysis can be easily enhanced to support the decision-making processes from different perspectives.